Anesthetic management of cesarean delivery for a parturient with Wilson's disease: A case report. Issue 20 (May 2018) - Wan, Yantong; Jiang, Xiaoqin; Lin, Xuemei
Abstract: Rationale: Wilson's disease (WD), or hepatolenticular degeneration, is an autosomal recessive disorder with a prevalence of 1:50, 000 to 1:100, 000 live births. Patient concerns: A 26-year-old primipara with WD was admitted to our hospital, due to awaiting delivery. Her main symptoms were slightly higher total bile acid (TBA) and bilateral depressed edema of lower limbs. Diagnosis: She was at 38 weeks and 4 days of gestation with a 15-year history of WD, controlled with penicillamine in the past and replaced by zinc preparations from three months before pregnancy. Outcomes: General anesthesia was successfully administered for a female with WD undergoing cesarean delivery. Lesson: General anesthesia can be administered in an asymptomatic primigravida with WD. Appropriate anesthetics choice can effectively minimize the rates of complications and sequelae.